Fenología de especies vegetales amazónicas a partir del conocimiento registrado en los herbarios - Flores Arévalo, Manuel (2008)
Elaborated an offer of use supported of the plant species diversity using the phenology as instrument that it complements to the knowledge of the plant species of the Peruvian Amazonia. The flowering and fructification was registered (phenology) of the Amazonian species, temperature and rainfall to correlate them with the variables; happening also the geographical distribution of the same ones. The capture of information realized in four herbalists, the herbalist AMAZ of the National University of the Peruvian Amazonia (Iquitos), the HUT of the National University of Trujillo, the USM of the National Major University of San Marcos (Lima) and the HV of the National University San Antonio Abad of the Cusco. The information was: scientific name and family; Georreferentiation, flowering, fructification and geographical location; Likewise, information of rainfall and temperature. Of 6237 species(kinds) of Angiospermae and Gymnospermae, distributed in 1406 kinds(genres) and 182 Families catalogued for the Peruvian Amazonia, a phenology calendar was prepared (flowering and fructification) with 2308 (37 %) of the plant species, of which, 8.5 % presents more than 10 records / species. That from 24 to 59 % of the plant species distributes in Loreto's department. The correlation of the flowering and fructification with the variables of temperature and rainfall they register varied indexes so much positive as negatives, indicating a relative influence of the climatic factors opposite to the phenology.